Effects of some new organic manures on yield, quality and N use efficiency of green soybean - YE Jing; Ho Ando; FU Jian-rong; Yuka Sasaki; Ken-ichi Kakuda (浙江大学学报. 农业与生命科学版, 2008)
Field experiment was carried out to study the effects of KEON (organic N extracted with KCI) and PEON (organic N extracted with phosphate buffer) from 4 kinds of organic wastes on the growth and N use efficiency of green soybean. The results show that the application of PM (poultry manures) could apparently improve the shoot dry weight, seed protein content and the yield by 20.4%, 17.8% and 38.0%, respectively, compared with regular chemical fertilizer applied. The application of OMM (organic mixed manures) could significantly improve the shoot dry weight, seed protein content and the yield by 33.2%, 16.2% and 32.5%, respectively, compared with regular chemical fertilizer applied. The positive correlation coefficiency between N use efficiency and KEON or PEON content was also observed with the correlation coefficient of 0.88 and 0.87 (P<0.05), respectively. Application of PM or OMM could greatly increase N use efficiency by 94.9% or 67.4% compared with regular chemical fertilizer applied.